Women's views of birth after cesarean section. Issue 12 (5th October 2021) - Sys, Dorota; Kajdy, Anna; Baranowska, Barbara; Tataj‐Puzyna, Urszula; Gotlib, Joanna; Bączek, Grażyna; Rabijewski, Michał
Abstract: Background: Vaginal birth is a safe mode of childbirth for the majority of women after cesarean section (CS). However, data show that women who have undergone a CS are more likely to have an elective CS (ECS) than a vaginal birth after CS (VBAC) in many areas of the world. Aim: This study aimed to review the literature about women's mode of birth preferences and attitudes and the underlying reasons for, and factors associated with, their preferences. Methods: This is narrative literature review. PubMed/MEDLINE and Scopus databases were searched, limiting the results to non‐interventional studies published between 1990 and 2020. Twenty‐one articles were included in the analysis. Results: The review found 34 different factors that influence women's preferences. Five factors influenced both VBAC and ECS preference, depending on the study. The most common factors having a dualistic effect on preference were: medical staff recommendation, doctor's opinion, and fear of pain. The most common factors were: desire to experience natural childbirth, faster/easier recovery, support from doctor's, and midwife's opinion. Among the factors influencing the preference for ECS, two were particularly prominent: predictability, controllability and comfortability of CS and the belief that CS is safer for the baby and/or mother. Conclusions: Our review showed that there are a variety of factors that influence women's preference for the mode of delivery after CS. Some of these have a dualistic effect according to the study. The key to making an informed decision regarding the mode of delivery is communication with medical professionals.